Targeting sustainable competitiveness in Croatia by implementation of "20 Keys" methodology - Marina Dabic; Mario Orac; Tugrul U. Daim (Journal of Innovation and Entrepreneurship, 2016)
Throughout the current wave of regulatory reforms, several theoretical models have been proposed that call for the emergence of instruments of self-regulation under some form of state supervision as part of the demand to improve product development performances aligned with awareness of environmental needs, to help with meeting regulation and to reduce the risk of production nonconformance. "20 Keys" is one example of a mass application of a methodology for raising sustainable development and holistic approach to competitiveness in new EU member the Republic of Croatia, and therefore, the aim of this study is to observe the results of the methodology application in Croatian companies. 20 Keys is a methodology that brings an integrated set of tools aimed at increasing overall productive efficiency and quality level with simultaneous reduction of costs. As it was shown in this paper, implementation success is coincident with senior management's active role in setting the main goals for implementation, assuring that suitable methods and tools are used, allocating resources appropriately and enabling communication within the company.
Keywords: 650; 20 Keys methodology; Managerial tool; Sustainable production; Lean management; Manufacturing companies